Hubungan Biaya Operasional, Waktu Kerja dan Lama Usaha Terhadap Income Pedagang Daging Babi di Pasar Tradisional - Sintya J. K Umboh (Jambura Journal of Animal Science, 2023)
This study was conducted based on the formulation of the problem that is how much operational costs and profits received by pork retailers and whether there is an effect of operational costs, working hours and length of business on the income of pork retailers in Amurang traditional market. The objectives of the study were (1) to determine the amount of operational costs and revenues received by pork retailers in Amurang traditional market, and (2) to analyze the effect of operational costs, working hours, and length of business on the income of pork retailers in Amurang traditional market. Determination of samples in this study using Purposive Sampling method. Consideration of the determination of the sample in this study is, pork retailers in the city of Amurang who have long been selling pork trading time of at least 3 years and already have a permanent place of sale in the traditional market Amurang, so that the number of respondents sebanhyak 15 people. The results obtained that, the average level of income (profit) Rp. 2.570.500 per day or average income (profit) per month Rp. 83,245,000 with an average weight of 4,050 kilograms of pork per month. Based on the analysis of the correlation coefficient value (r) of 0.95 gives the meaning that, koefisen variables X1 (operating costs), X2 (working hours), and X3 (long business) has a strong relationship (correlation) to the income level of pork retailers by 0.95 the strong relationship with the income level of variables measured can be explained through the coefficient of determination (R) 0.90 means that the income of pork retailers is 90% influenced by variables X1 (operating costs), X2 (working hours) and X3 (long business), while 10% is explained by other variables that are not included in the analysis model. Based on the results of the study concluded that the level of income earned pork retailers in the traditional market Amurang is Rp. 83,245,000 per month with an average weight of the whole piece of pork as much as 4,050 kilograms per month. Operational costs, working hours and length of time simultaneously affect the income of pork retailers in Amurang traditional market. Partially operational costs and length of business affect the income while the variable working hours do not affect the income of pork retailers in Amurang traditional market.